151. Evaluation of Pneumococcal Vaccine Effectiveness Against Invasive Pneumococcal Disease Among US Medicare Beneficiaries ≥65 Years Old. (26th November 2018) - Pilishvili, Tamara; Almendares, Olivia M; Nanduri, Srinivas; Warnock, Rob; Wu, Xiyuan; McKean, Stephen; Kelman, Jeffrey; Farley, Monica M; Schaffner, William; Thomas, Ann; Reingold, Arthur; Harrison, Lee H; et al.
Abstract: Background: Pneumococcal conjugate vaccine (PCV13) was recommended in series with PPSV23 for all US adults ≥65 years in late 2014. We evaluated effectiveness of PCV13 against invasive pneumococcal disease (IPD) among Medicare beneficiaries ≥65 years old to assess this new policy. Methods: We linked records for IPD cases (pneumococcus isolated from sterile sites) in persons ≥65 years old identified through Active Bacterial Core surveillance with those of Medicare beneficiaries. Isolates were serotyped and classified as PCV13 (with or without cross-reacting type 6C), and nonvaccine types. We selected Medicare beneficiaries with no record of IPD or pneumonia as controls, and matched to cases on age, residence census tract, and length of Medicare enrollment; we included all eligible controls. Vaccination and medical histories were obtained through Medicare. We estimated vaccine effectiveness (VE) as 1 minus the IPD odds ratio for vaccinated (PCV13) vs. unvaccinated (no PCV13 or PPSV23) persons using conditional logistic regression, adjusted for sex and underlying conditions. Results: From 2, 246 IPD cases identified in 2015–2016, 1, 017 (45%) were matched to Medicare beneficiaries. After excluding cases in persons residing in long-term care facilities or with <1 year of Medicare enrollment, we included 699 eligible cases and 10, 152 controls in our analysis. PCV13-types (+6C) accounted for 164 (23%) cases, and serotype 3 was the most common PCV13-type. Case patients were more likely than controls to have one or more chronic (88% vs. 58%) or immunocompromising (54% vs. 32%) conditions present. Fourteen percent, 22%, and 8% of case patients, and 18%, 21%, and 8% of controls received PCV13 only, PPSV23 only, or both vaccines, respectively. PCV13-only VE against PCV13-types was 36% (95% CI −18, 65%). When we included type 6C with PCV13-types, VE was 67% (95% CI 11, 88%). PCV13 showed similar effectiveness against PCV13 type (+6C) IPD among adults >75 years of age (VE 61%, 95% CI 14, 82). VE was 26% (95% CI −58, 65%) against serotype 3 and 67% (95% CI 11, 88%) against other PCV13-types (+6C). PCV13 was not effective against nonvaccine types. Conclusion: PCV13 was effective in preventing IPD caused by PCV13 types when excluding type 3; no effectiveness was demonstrated against serotype 3. Disclosures: W. Schaffner, Merck: Member, Data Safety Monitoring Board, Consulting fee. Pfizer: Member, Data Safety Monitoring Board, Consulting fee. Dynavax: Consultant, Consulting fee. Seqirus: Consultant, Consulting fee. SutroVax: Consultant, Consulting fee. Shionogi: Consultant, Consulting fee.